The Urgency Of The Existence Of Brainware Management System In Companies From The Perspective of A Welfare Law State To Win The Competition - Nugraha Pranadita; Agus Rahayu; Lili Adi Wibowo; Ridwan Purnama (Universitas Dharma Wacana, 2026)
Labor costs, a major component of fixed costs, are certain to continue to rise annually. This is not due to improvements in labor quality and quantity, or labor scarcity, but rather to the obligation to comply with the law. Some industries believe that innovation will increase competitiveness, when in fact, innovation also creates diseases that kill the industry itself or create monsters that destroy other industries. To win the competition, there are external factors that are given, and there are also a few internal factors that can be customized to give the industry some breathing room. One of these customized internal factors is the soft side of human resources within the company and the opportunities created by technological developments and laws and regulations. The Brainware Management System is one tool that can be used by industries to win the competition by leveraging developments in artificial intelligence technology and legal protection in the current digital era. How urgent is the existence of a brainware management system in companies from the perspective of a welfare state to win the competition? The research method used here is qualitative research. In qualitative research, the population is referred to as the social situation, which consists of three elements: Place, actors, and activities interact with one another. The paradigm used is a methodological paradigm, which concerns how research should be conducted by researchers; understanding through the eyes of the researcher. In this case, specific phenomena can be explained by the researcher's a-priori knowledge. The important role of the brainware management system in companies is to reduce labor/worker honorarium/salary costs, which are carried out appropriately and legally. This ensures that companies can compete in the industry with a low-cost strategy, the public can obtain jobs with honorariums/salaries in accordance with statutory regulations, and the government can fulfill its constitutional duty to improve public welfare through the availability of employment opportunities